2016
DOI: 10.1016/j.jcms.2015.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Osteonecrosis of the jaw in patients treated with denosumab for metastatic tumors to the bone: A series of thirteen patients

Abstract: This case series describes the course of osteonecrosis of the jaw (ONJ) in thirteen patients with metastatic bone tumors treated solely with denosumab. Patients on denosumab may be more prone to developing ONJ even without a risk/precipitating factor and they may develop ONJ early in their denosumab therapy. The outcomes of ONJ in ten patients following a period of denosumab discontinuation after the onset of ONJ were: 3 had complete resolution of symptoms, 4 patients’ ONJ progressed, 2 patients’ ONJ was uncha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…Osteonecrosis of the jaw caused by non-bisphosphonate therapy has been characterized as anti-resorptive-related osteonecrosis of the jaw, and the risk for this complication is considered higher in patients who undergo dental procedures while receiving denosumab or other anti-resorptive treatment. 59 Owosho et al 60 reported 13 cases of osteonecrosis of the jaw among patients who were receiving denosumab monotherapy for metastatic bone tumors. Dental extraction prior to osteonecrosis of the jaw was reported in 7 patients.…”
Section: Complications Of Denosumab Therapymentioning
confidence: 99%
“…Osteonecrosis of the jaw caused by non-bisphosphonate therapy has been characterized as anti-resorptive-related osteonecrosis of the jaw, and the risk for this complication is considered higher in patients who undergo dental procedures while receiving denosumab or other anti-resorptive treatment. 59 Owosho et al 60 reported 13 cases of osteonecrosis of the jaw among patients who were receiving denosumab monotherapy for metastatic bone tumors. Dental extraction prior to osteonecrosis of the jaw was reported in 7 patients.…”
Section: Complications Of Denosumab Therapymentioning
confidence: 99%
“…These investigations led to the assumption and the hypothesis that methamphetamine abuse might be—in addition to bisphosphonates (e.g., alendronate, zoledronate), anti-RANKL antibodies (denosumab), anti-VEGF antibodies (bevacizumab), tyrosinkinase inhibitors (sunitinib), estrogen receptor modulators (e.g., Raloxifen) and methotrexate—a further possible reason for MRONJ development [ 5 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: “Meth Mouth” and Jaw Necrosismentioning
confidence: 99%
“…To elucidate the influence of denosumab on the development of ONJ, the present study also reviewed the literature, including clinical trials (310) and case reports (1121), in regards to the prevalence, clinical characteristics and management of ONJ associated with denosumab.…”
Section: Introductionmentioning
confidence: 99%